The development of Vietnamese constitutionalism: from modern to contemporary era - Dao, Tri Uc (2020)
Modern Vietnamese constitutionalism is seen as the product of a combination of national traditionsand ideological values inherited from the country history and the process of absorbing legal system in unique ways. Among the traditional values influencing the formation of constitutional thought, it is worth mentioning the autonomy of village management in the local governance tradition. The stability and durable vitality of the autonomous rural commune regime were preserved and acknowledged even during the period when Vietnam became a French colony (1858-1945).Today’s Vietnamese constitutionalism is based on the tradition of tolerance and humanity, which facilitates access to fair values and justice as well as to meet the requirements of respect and protection of human rights, the legitimacy of power and the integrity of the people on duty. The content of modern Vietnamese constitutionalism is determined according to the logic of the tradition of social solidarity which, in the language of modern Constitutionalism, is social consensus with guarantees by constitutional institutions and corresponding legislation as well as the necessary Constitutional guarantee mechanism which remains as the concerning future issue.In addition, the paper also discusses the barriers to the completion of Vietnamese constitutionalism such as the influence of the ownership regime, power centralism, and low legal awareness which were all products of smallholder agriculture and past long wars.